PENGARUH MODIFIKASI PANAS OIL HEAT TREATMENT TERHADAP PERUBAHAN WARNA DAN BERAT PADA BAMBU BETUNG (Dendrocalamus asper) DAN BAMBU ANDONG (Gigantochloa pseudoarundinacea) - Suri, Intan Fajar; Hidayat, Wahyu; Febryano, Indra Gumay; Hilmanto, Rudi; Hadida, Ratu Husaina; Awandi, Hafizh (MAKILA, 2024)
Betung bamboo (Dendrocalamus asper) and andong bamboo (Gigantochloa pseudoarundinacea) are non-timber forest products that can be used as a substitute for wood. However, both bamboos have light colors that are less aesthetic and susceptible to fungal and pest damage. Therefore, it is necessary to modify the bamboo. One of the modification methods used is oil heat treatment (OHT). This research aims to determine the effect of OHT on the color of betung and andong bamboo. This research was carried out the OHT using palm oil at temperatures of 180°C, 200°C, 220°C and 240°C for 2 hours. Color parameter measurements were observed using a colorimeter that implemented the CIE-Lab color system. The color parameters measured include brightness (L*), red/green chromaticity (a*), yellow/blue chromaticity (b*), and overall color change (∆E*). The percentage of bamboo weight loss after OHT was also observed. The research results show that the brightness value (L*) of betung bamboo and andong bamboo has decreased, so that the color becomes darker as the temperature increased. The a* and b* values decreased at all temperatures and durations. In addition, the value of ∆E* increased at all temperatures with a total change showing a value > 12. The decrease in weight of betung bamboo occurred at all temperatures. This heat treatment can make the bamboo color darker and more exotic, thereby increasing the added value of the product and improving the quality of bamboo from fungi and pests due to cellulose degradation.